FORMATION OF ELEMENTARY SCHOOL PUPILS' ORTHOGRAPHIC COMPETENCE IN THE CONDITIONS OF RUSSIAN AND UKRAINIAN BILINGUALISM - Ріяна Зіядінова; Віра Каленська (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article reveals the peculiarities of the formation of orthographic competence of elementary school pupils in terms of Russian and Ukrainian bilingualism. An analysis of scientific and methodical literature on the given problem has been made. Also, there has been carried out a comparative analysis of the spelling rules ofthe Russian and the Ukrainian languages at primary school. The difficulties faced by students in the process of simultaneous study of the Ukrainian and Russian spelling have been described in this research. There has also been made a quantitative and qualitative analysis of the the research and experimental work on the formation of orthographic competence of elementary school pupils in terms of Russian and Ukrainian bilingualism.